A review for Japanese auroral records on the three extreme space weather events around the International Geophysical Year (1957–1958). Issue 1 (8th March 2022) - Hayakawa, Hisashi; Ebihara, Yusuke; Hata, Hidetoshi
Abstract: Solar Cycle 19 was probably the greatest solar cycle over the last four centuries and significantly disrupted the solar‐terrestrial environments with a number of solar eruptions and resultant geomagnetic storms. At its peak, the International Geophysical Year (IGY: 1957–1958) was organised under international collaborations and benefitted scientific developments, capturing multiple unique extreme space weather events including the third and fourth greatest geomagnetic storms in the space age. In this article, we review and analyse original records of Japanese auroral observations around the IGY. These observations were organised by Masaaki Huruhata in collaboration with professional observatories and citizen contributors. We have digitised and documented these source documents, which comprise significant auroral displays in March 1957 (minimum Dst = −255 nT), September 1957 (minimum Dst = −427 nT), and February 1958 (minimum Dst = −426 nT). These records allow us to visualise temporal and spatial evolutions of these auroral displays, reconstruct their equatorward auroral boundaries down to 41.5°, 38.3°, and 33.3° in invariant latitudes, and contextualise their occurrences following contemporary geomagnetic disturbances. Our results have been compared with significant auroral displays during other extreme space weather events. These aurorae generally showed reddish colourations occasionally with yellowish rays. Their colourations are attributed to reddish oxygen emission and its mixture with greenish oxygen emission. Overall, these archival records provide the references for future discussions on the auroral activities during the uniquely intense and extreme space weather events. Abstract : A sample auroral drawing in the daily ledger of Niigata Local Meteorological Office, courtesy of © Niigata Local Meteorological Office.